Abstracts of Symposium II: Acute Coronary Syndrome: The Obstructive Plug - Symposium II: Acute Coronary Syndrome: The Obstructive Plug (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Abstracts of Symposium II: Acute Coronary Syndrome: The Obstructive Plug